Juridical Review of Civilians Wearing Rfs Car Plates Reviewed by Law Number 22 Years 2009 on Traffic and Road Transport - Ahmad Zulfa Rangkuti; Abdul Hakim; Maya Jannah (Journal of Social Research, 2023)
This study aims to find out and analyze the regulations regarding the manufacture of "RFS" license plates on vehicles. As well as knowing and analyzing the legal consequences arising from making license plates on the roadside. This research belongs to the normative type of research. So it can be known that civil society using RFS car plates is a special license plate code ending in 'RFS' which is only given to certain circles and is not commonly used in the general public. The use of special license plate codes is regulated in the Regulation of the Chief of Police No. 3 of 2012 concerning the Issuance of Recommendations for Motor Vehicle Number Letters (STNK) and Special and Secret Motor Vehicle Number Signs (TNKB) for Official Motor Vehicles.